Partial Discharge Analysis on-site in Various High Voltage Apparatus - Kim, D.; Abu-Siada, Ahmed (2018)
© 2018 IEEE. Partial discharge (PD) analysis is one of the most reliable non-destructive tests to clarify the quality of the insulation and to evaluate the life expectancy of high voltage (HV) devices. To perform PD testing and analysis accurately, it is important to select the correct method with respect to various sorts of the specimen. This paper aims at supporting HV engineers and asset managers to select a correct PD method and to make a clear maintenance plan. Also, this paper presents the difference between on and off PD analysis techniques, and the proper PD testing for rotating machines, switchgears and power cables with a case study and practical suggestions.